2010
DOI: 10.1021/ie901980c
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Oil Deacidification by Amberlyst: Study of the Catalyst Lifetime and a Suitable Reactor Configuration

Abstract: Deacidification of crude vegetable oils containing high amounts of free fatty acids is the first step toward low-cost biodiesel production. In order to lower the acid content, the most popular method is based on an esterification process carried out with methanol and using Amberlysts as solid acid heterogeneous catalysts. This process was deeply investigated in recent years with good results. At the moment, the lifetime of the catalyst is the most crucial issue in industrial applications. With the aim of inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…As already evidenced in previous studies of the authors [5,7], the experiment carried out in absence of the catalyst showed no FFA conversion.…”
Section: Catalytic Testssupporting
confidence: 75%
See 3 more Smart Citations
“…As already evidenced in previous studies of the authors [5,7], the experiment carried out in absence of the catalyst showed no FFA conversion.…”
Section: Catalytic Testssupporting
confidence: 75%
“…FFA are highly sterically hindered molecules, which might not be able to penetrate inside the pores as narrow as those of the catalysts here synthesized. The importance of the location of the active sites on the outer surface of the catalyst has already been evidenced by the authors in a previous work for other kinds of materials [7]. Therefore, it is possible to assume that, in the present case, the active sites located on the catalyst's outer surface are the most responsible for the reaction to occur.…”
Section: Catalytic Testsmentioning
confidence: 55%
See 2 more Smart Citations
“…In a previous paper 14 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 catalytic bed, the FFA esterification reached in fact the thermodynamic plateau, corresponding to FFA conversion greater than 90%. This means that the final FFA concentration in the oil was about 0.3% wt , lower than the set limit of 0.5% w for biodiesel processes production.…”
Section: Resultsmentioning
confidence: 86%